2007
DOI: 10.1186/1749-799x-2-22
|View full text |Cite
|
Sign up to set email alerts
|

Acromioclavicular joint dislocation: a comparative biomechanical study of the palmaris-longus tendon graft reconstruction with other augmentative methods in cadaveric models

Abstract: BackgroundAcromioclavicular injuries are common in sports medicine. Surgical intervention is generally advocated for chronic instability of Rockwood grade III and more severe injuries. Various methods of coracoclavicular ligament reconstruction and augmentation have been described. The objective of this study is to compare the biomechanical properties of a novel palmaris-longus tendon reconstruction with those of the native AC+CC ligaments, the modified Weaver-Dunn reconstruction, the ACJ capsuloligamentous co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Superficial wound infection is not uncommon owing to the extensive soft-tissue damage and foreign body reaction to non-absorbable materials. [32][33][34] Other complications associated with the Surgilig include coracoid fracture, screw loosening in the clavicle, and distal clavicular osteolysis. 10,11,35 Limitations of our study included nonrandomisation, a small sample size, no objective assessment (although radiographic appearance does not correlate with the clinical outcome 22 ), and possible observational bias owing to lack of blinding.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial wound infection is not uncommon owing to the extensive soft-tissue damage and foreign body reaction to non-absorbable materials. [32][33][34] Other complications associated with the Surgilig include coracoid fracture, screw loosening in the clavicle, and distal clavicular osteolysis. 10,11,35 Limitations of our study included nonrandomisation, a small sample size, no objective assessment (although radiographic appearance does not correlate with the clinical outcome 22 ), and possible observational bias owing to lack of blinding.…”
Section: Discussionmentioning
confidence: 99%
“…Modi et al 10) reported that the goal of fixation of ACJ is to restore the CCD in order to allow healing of the ruptured ligaments. Also, Luis et al 26) reported that coracoclavicular ligament repair is unnecessary with hook plates because anatomical reduction is done. Therefore, using hook plate in anatomical reduction of ACJ dislocation, which is advantageous for superoinferior displacement reduction, will normalize CCD and ACD to achieve superoinferior reduction and yield coracoclavicular ligament healing effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, remove of the clavicular hook plate often induced recurrence of the AC joint dislocation. In all, the above fixation methods are non-anatomic reconstruction which cannot restore the anatomic structure of the CC ligament and AC ligament, and the anatomical functions cannot fully restore though the above problems are avoided post-operation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%